High contrast fluorescence polarization microscopy through double tagged photoswitchable fluorescent proteins - Lukas J. Münker; Manuel Hohgardt; Andreas Albrecht; Dominik Pfennig; Jan S. Tegtmeier; Andreas Holz; Marta Zagrebelsky; Martin Korte; Peter J. Walla (npj Imaging)
Abstract We demonstrate that rigid anchoring of fluorescent proteins through double tagging (FPs) in living cells can significantly enhance the contrast in fluorescence polarization microscopy (FPM) by locking the transition dipole moment orientations to the sample’s structures. We applied double tagging of reversibly photoswitchable FPs (dt-rsFPs) to membranes and present a novel camera frame-separated switching pulse scheme that allows effective narrowing of the angle range of excited dt-FP also in living cells (frame-separated excitation polarization angle narrowing, FrExPAN). The principle of rigid anchoring allows specific selection of signals from different structural cell parts with slightly different orientations and is broadly applicable. FrExPAN imaging with dt-rsFPs double-tagged to membranes of living HeLa cells and living hippocampal neurons is demonstrated. We discuss potential implications for orientational contrast imaging as well as super-resolution by polarization demodulation (SPoD) methods.